In vivo degradation and endothelialization of an iron bioresorbable scaffold - Wenjiao Lin; Hongjie Zhang; Wanqian Zhang; Haiping Qi; Gui Zhang; Jie Qian; Xin Li; Li Qin; Haifeng Li; Xiang Wang; Hong Qiu; Xiaoli Shi; et al. (Bioactive Materials, 2021)
Detection of in vivo biodegradation is critical for development of next-generation medical devices such as bioresorbable stents or scaffolds (BRSs). In particular, it is urgent to establish a nondestructive approach to examine in vivo degradation of a new-generation coronary stent for interventional treatment based on mammal experiments; otherwise it is not available to semi-quantitatively monitor biodegradation in any clinical trial. Herein, we put forward a semi-quantitative approach to measure degradation of a sirolimus-eluting iron bioresorbable scaffold (IBS) based on optical coherence tomography (OCT) images; this approach was confirmed to be consistent with the present weight-loss measurements, which is, however, a destructive approach. The IBS was fabricated by a metal-polymer composite technique with a polylactide coating on an iron stent. The efficacy as a coronary stent of this new bioresorbable scaffold was compared with that of a permanent metal stent with the name of trade mark Xience, which has been widely used in clinic. The endothelial coverage on IBS was found to be greater than on Xience after implantation in a rabbit model; and our well-designed ultrathin stent exhibited less individual variation. We further examined degradation of the IBSs in both minipig coronary artery and rabbit abdominal aorta models. The present result indicated much faster iron degradation of IBS in the rabbit model than in the porcine model. The semi-quantitative approach to detect biodegradation of IBS and the finding of the species difference might be stimulating for fundamental investigation of biodegradable implants and clinical translation of the next-generation coronary stents.